Molecular Epidemiology of Carbapenem-Resistant Acinetobacter baumannii Strains Isolated at the German Military Field Laboratory in Mazar-e Sharif, Afghanistan - Paul G. Higgins (MDPI AG, 2021)
The study was performed to provide an overview of the molecular epidemiology of carbapenem-resistant Acinetobacter baumannii in Afghanistan isolated by the German military medical service during the Afghanistan conflict. A total of 18 isolates were collected between 2012 and 2018 at the microbiological laboratory of the field hospital in Camp Marmal near Mazar-e Sharif, Afghanistan, from Afghan patients. The isolates were subjected to phenotypic and genotypic differentiation and antimicrobial susceptibility testing as well as to a core genome multi-locus sequence typing (cgMLST) approach based on whole-genome next-generation sequence (wgNGS) data. Next to several sporadic isolates, four transmission clusters comprising strains from the international clonal lineages IC1, IC2, and IC9 were identified. Acquired carbapenem resistance was due to blaOXA-23 in 17/18 isolates, while genes mediating resistance against sulfonamides, macrolides, tetracyclines, and aminoglycosides were frequently identified as well. In conclusion, the assessment confirmed both the frequent occurrence of A. baumannii associated with outbreak events and a variety of different clones in Afghanistan. The fact that acquired carbapenem resistance was almost exclusively associated with blaOXA-23 may facilitate molecular resistance screening based on rapid molecular assays targeting this resistance determinant.